OPTIMALISASI RETRIBUSI PARIWISATA TERHADAP PENINGKATAN PENDAPATAN ASLI DESA DI DESA KERTAYASA - Irman Firmansyah; R Neneng Rina Andriani; Rani Rahman; Nur Jannah Abdi Aziz (Jurnal Pasca Dharma Pengabdian Masyarakat, 2023)
The purpose of this community service activity on the Community Service for the Application of Science and Technology Program to the community (PbM-PPIM) is intended for Village Offices and BUMDES that manage tourist villages and are located in Kertayasa Village, Cijulang District, Pangandaran Regency. The importance of this training related to the optimisation of tourism levies for village offices and BUMDES is to increase Village Original Revenue. The problems raised are the lack of resources and the less than optimal management of tourism village levies. In fact, if managed properly, it will encourage the growth of economic businesses and the welfare of village communities in a sustainable manner. One of the potentials that can be explored is that the tourism sector levy in this village is quite high. This opportunity must be utilised by the manager in order to increase the income and welfare of the community in general, and increase the revenue of the village's original income in particular. Thus, special counselling is needed so that the management of tourism villages, especially on tourism levies, becomes better. The results of the activity showed that the village government and community felt helped in improving the utilisation of tourism potential and optimising tourism levies in Kertayasa Village.